Outreach initiatives of academic libraries: A bibliometric analysis based on the Scopus database - Johoran, S. Shabnam (University of Colombo, 2025)
Organizations worldwide are increasingly realizing the value of functioning in a socially responsible manner. The International Standard ISO 26000 provides guidance on social responsibility for all types of organizations. Academic libraries, as service-oriented institutions, play a crucial role in community engagement and should emphasize outreach initiatives as a means of fulfilling their social responsibility. Despite their potential to impact communities positively, there is limited comprehensive knowledge on how outreach efforts are explored in scholarly research. This study aims to identify and analyze research trends related to outreach initiatives in academic libraries by mapping bibliometric patterns of publications indexed in the Scopus database. The specific objectives of the study include mapping the year-wise distribution of papers, examining the authorship patterns, determining the degree of author collaboration, identifying the author’s contribution based on the country, and mapping keyword occurrences. “Outreach*” OR “Community Engagement” AND “Academic Libraries” OR “Academic Librarians” OR “University Libraries” OR “University Librarians”, limited to article titles and keywords to ensure relevance. The search was performed without indicating a specific period. Publish or Perish Software was used to extract the research publications from the Scopus database. Microsoft Excel and VOS Viewer applications were used for data analysis and visualization. Following the PRISMA flowchart, 53 relevant research articles were selected for analysis. The first research article on outreach initiatives in academic libraries was published in 2000 in the Scopus database. The findings indicate from 2011 to 2017 has been the prominent period in research publications on outreach initiatives in academic libraries. Most articles were co-authored, reflecting a high degree of collaboration among researchers. The United States of America has been the most productive country in research on outreach initiatives in academic libraries. Commonly occurring keywords included “Academic Library”, “Outreach”, “Community Engagement”, “Promotion”, and “Opportunity”. This bibliometric study offers valuable insights for researchers and practitioners interested in understanding the scholarly landscape of outreach efforts in academic libraries.
Keywords: Outreach initiatives; Academic libraries; Bibliometrics; Scopus database